1935
DOI: 10.1128/jb.30.6.559-571.1935
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Bacteria Capable of the Fermentation of Sulfite Waste Liquor

Abstract: Sulfite waste liquor (s.w.l.) results from the manufacture of cellulose pulp by the acid-sulfite process. It contains about 11 per cent of material, in solution, which consists of soluble ligninsulfonic salts of calcium (60 to 70 per cent), hexose sugars (12 to 20 per cent), pentosans and pentoses (4 to 5 per cent), their various oxidation products, acetic and formic acids (0.5 to 1.0 per cent), and traces of other organic substances. When discharged into small natural waterways it frequently causes serious tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1940
1940
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A tryptone (.5 per cent) dextrose (.5 per cent) broth with reduced iron and sodium sulfite (.25 per cent) turned nearly black as did lead acetate papers suspended in the tubes. A test to determine the tolerance of sulfite was suggested by the paper of Partansky and Henry (1935 .... Corn Mash: Corn mash cultures with and without liver, McClung and McCoy (1934), showed only traces of gas and no liquefaction of the medium, corresponding to Group la, C1. pastezLrianum type of McCoy, et al (1930).…”
Section: Pilysiological Characteristicsmentioning
confidence: 99%
“…A tryptone (.5 per cent) dextrose (.5 per cent) broth with reduced iron and sodium sulfite (.25 per cent) turned nearly black as did lead acetate papers suspended in the tubes. A test to determine the tolerance of sulfite was suggested by the paper of Partansky and Henry (1935 .... Corn Mash: Corn mash cultures with and without liver, McClung and McCoy (1934), showed only traces of gas and no liquefaction of the medium, corresponding to Group la, C1. pastezLrianum type of McCoy, et al (1930).…”
Section: Pilysiological Characteristicsmentioning
confidence: 99%
“…Soil is one of the greatest reservoirs of bacterial abundance and biodiversity [6]. To the best of our knowledge, at least 18 novel species of the genus Clostridium have been proposed with the type strains isolated from various soils (C. arbusti [7], C. argentinense [8], C. chromiireducens [9], C. combesii [10], C. cylindrosporum [11], C. fungisolvens [12], C. gelidum [13], C. kogasense [14], C. nitritogenes [10], C. nitrophenolicum [15], C. manihotivorum [16], C. oryzae [17], C. phytofermentans [18], C. polyendosporum [5], C. saccharoperbutylacetonicum [19], C. sartagoforme [20], C. sporogenes [21] and C. thailandense [22]), suggesting that soil is one of the major sites for isolating the genus Clostridium. It has been reported that Clostridia have been isolated at particularly high prevalence and abundance in flooded paddy soils [23][24][25].…”
Section: Introductionmentioning
confidence: 99%